Prevention of Tax Avoidance by a Notary on Stock Grant Deeds Affected by Private Relationships - Harnjo, Edline Annetta; Susanto, Henro; Gunawan, Edy (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Grant transactions are often considered by the public to be an exception to the object of Income Tax. This provision is a mandate of the Income Tax Law by considering the relationship between the giver and recipient of the grant. Stock grant transactions can be excluded as a tax object if they are given to blood relatives in a straight line of one degree and there is no relationship with business, work, ownership, or control between the two parties. Stock grant transactions are carried out with a deed of transfer of rights to shares which can be done privately or by notarial deed. Notaries as public officials who are authorized to make authentic deeds have an obligation to provide recommendations and ensure supporting documents attached by the parties. In terms of preventing tax avoidance, notaries can provide consultation and education based on their general understanding of taxation and review data related to the parties attached to the deed. Based on this, the role of notaries in carrying out their duties in preventing tax avoidance in stock grant transactions will be discussed.